Parâmetros produtivos de búfalos mediterrâneo em pastagem de Brachiaria humidicola - (:unkn) unknown (Instituto Brasileiro de Informação em Ciência e Tecnologia, 1993)
The work is being developed in the Laboratory of Animal Nutrition of EMBRAPA - CPATU, in Belém-Pa, and consists in the evaluation of a production model, with the objective of determining the production rates of Mediterranean buffaloes, explored in cultivated Brachiaria humidicola pasture on terra firme. The work is carried out by monitoring and controlling the feeding, reproduction, health and pasture management components of the production system. The herd used consists of 30 females of reproductive age. Results obtained in the 1991/92 period showed values of 1,402.7 and 1,405.4 for average milk production/cow in the 1st and 2nd lactation, with an average daily milk production of 5.6 and 6.0 and 250 and 234 for lactation length, respectively. The postpartum weights were 530.3 and 553.8 kg in the 1st and 2nd calving, and the age at 1st calving and calving interval were 36 months and 43l.7 days, respectively. Data related to offspring showed values of 37.4 and 34.5 kg for birth weight, 160.9 and 151.5 kg at 6 months of age and 254.4 and 232.2 kg at 1 year of age for males and females respectively. The results obtained so far are satisfactory, however, the analysis by component of the system will allow more information to be obtained that will contribute to the improvement of the production indexes of buffaloes in this production model.
Production parameters of Mediterranean buffaloes on Brachiaria humidicola pasture
Keywords: Produção; Búfalos; CNPQ::CIENCIAS BIOLOGICAS::ZOOLOGIA